Soil Quality on area of Selective Cutting and Strip Planting System (TPTJ) in IUPHHK/HA PT. Sari Bumi Kusuma Central Kalimantan Province - Prijanto Pamoengkas; Adytia Pradnya Murti (Jurnal Silvikultur Tropika, 2011)
Rapid forest exploitations can cause forest degradation, and eventually may cause the global climate change, because of that, the balance of the forest sustainability must be kept as well. The implementation of silviculture system called Selective Cutting and Strip Planting System is one of several forest harvesting method that consider the importance of forest sustainability. Practically, the system has never been tested to the last cycle. So, it is necessary to conduct some evaluation to the method to assure its sustainability. Estimation of soil quality is one of several ways to evaluate the effectiveness of silviculture implementation on a forest area, Since the soil is one of the major factor that influencing the growth of vegetations, then its quality can be used as an indication of conservation of forest productivity.